2021
DOI: 10.1007/s11356-021-16038-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of hearing loss with total and cause-specific mortality in US adults

Abstract: We expected to explore the associations of hearing loss and hearing thresholds at different frequencies with total and cause-speci c mortality. Methods 11,732 individuals derived from the National Health and Nutrition Examination Survey (NHANES) 1999-2012 were included in this study. Data of death was extracted from the NHANES Public-Use Linked Mortality File through December 31, 2015. Cox proportional hazards models were used to explore the associations between hearing loss, hearing thresholds at different fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, smoking is related to other lifestyles that may adversely affect health. Another study found that participants who do not engage in physical activities have an increased risk of death caused by HL in different hearing levels [ 46 ]. As reported previously, severe hearing loss is also associated with slower walking speed [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, smoking is related to other lifestyles that may adversely affect health. Another study found that participants who do not engage in physical activities have an increased risk of death caused by HL in different hearing levels [ 46 ]. As reported previously, severe hearing loss is also associated with slower walking speed [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two hypotheses have been investigated to understand the connection between hearing loss and cognitive decline: one suggests that cognitive decline precedes hearing loss, and the other attributes hearing loss as the precursor to cognitive decline [8]. In addition to the implications for psychiatric disorders and cognitive decline, a study investigating findings reported by the National Health and Nutrition Examination Survey conducted from 1999 to 2007 revealed that speech-frequency hearing loss is significantly associated with increased heart disease mortality and overall death rates [9]. Hearing loss should not be viewed solely as an impairment of the sensory system but as a condition with wide-ranging consequences for an individual's overall health.…”
Section: Introduction 1hearing Lossmentioning
confidence: 99%
“…VI and HI are some of the largest contributors to the global disease burden for older adults, resulting in a signi cant economic burden 4 . Both VI and HI have been associated with several adverse effects such as low quality of life 1 , depression 5 , falls 2 , lower cognitive function 6 , and even increased risk of mortality 7,8 . Co-occurring vision and hearing impairment is called dual sensory impairment (DSI) 5 .…”
Section: Introductionmentioning
confidence: 99%